THE CHOICE OF CODES USED BY TWO ANNOUNCERS OF DJ FM AND SS FM RADIO STATIONS IN THEIR ADVERTISEMENTS - Nomeliance Delivia Nabubois; Henny PS Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2014)
This thesis is a study of the choice of codes used by the announcers of DJ FM and SS FM radios in their advertisements, consisting of twenty advertisements from both radios. I applied some theories of codes from Wardaugh (2006), Stockwell (2002), and Holmes (2001) as my main theories. Also, I used the theory of Age and Linguistic choice from Coulmas (2005), and Marketing and Language Choice from Victor (2007) as my supporting theories. The subjects are two announcers of DJ FM and SS FM radios which are in the phase of young adulthood. Furthermore, I found that the announcers from both radio stations used Standard Indonesia as their main code. The conclusion is the target audience of DJ FM and SS FM did not influence the way the announcers chose their codes.